The Example of Ismuba Teacher Leadership in Shaping the Character of Responsibility at SD Muhammadiyah - Santoso Santoso; Abdul Hopid; Farid Setiawan; Mhd. Lailan Arqam (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Character and responsibility education in elementary school students still faces various challenges, such as low discipline, a lack of awareness of worship, and weak responsibility for academic and social tasks. This condition shows that character formation is not enough only through cognitive teaching, but requires real examples from educators, especially teachers, as moral leaders in schools. Based on these conditions, ISMUBA (Al-Islam, Muhammadiyahan, and Arabic) teachers have a strategic role in instilling the character of responsibility through leadership examples. This study aims to describe the form of leadership role model of ISMUBA teachers, the character of student responsibility, and the role of exemplary leadership of ISMUBA teachers in shaping the character of student responsibility at SD Muhammadiyah. This study uses a descriptive qualitative approach with the subjects of school principals, ISMUBA teachers, and students. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model with data validity tests through triangulation. The results of the study show that the leadership example of ISMUBA teachers is realized through discipline, consistency in the implementation of worship, habituation of responsibility attitudes, and educational social interaction. The character of student responsibility is reflected in compliance with school rules, awareness in carrying out worship, and responsibility for academic and social tasks.